2016
DOI: 10.3945/jn.115.228148
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Broccoli Lessens Development of Fatty Liver and Liver Cancer in Mice Given Diethylnitrosamine and Fed a Western or Control Diet

Abstract: Long-term consumption of whole broccoli countered both NAFLD development enhanced by a Western diet and hepatic tumorigenesis induced by DEN in male B6C3F1 mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
44
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 64 publications
5
44
0
Order By: Relevance
“…However, a diet high in fat (e.g., lard from bacon consumption) has long been considered as a risk factor for IBD and colon cancer [29,30]. Therefore, although lard contains certain amount of linoleic acid, the diet in this study is a widely accepted high (lard) fat diet for animal models to address diet-induced obesity issue which is partially related to a Western diet [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…However, a diet high in fat (e.g., lard from bacon consumption) has long been considered as a risk factor for IBD and colon cancer [29,30]. Therefore, although lard contains certain amount of linoleic acid, the diet in this study is a widely accepted high (lard) fat diet for animal models to address diet-induced obesity issue which is partially related to a Western diet [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that broccoli protects against the development of NAFLD and liver adenomas in mice fed an HF diet and treated with diethylnitrosamine (an agent that induces hepatocellular carcinoma in mice). Mice fed an HF diet (19% fat and 31% sucrose) and 10% broccoli had decreased liver weight, hepatic TGs, plasma ALT concentrations, and number of liver nodules and adenomas compared with mice fed an HF diet without broccoli (93). In this study, mice were started on a Western diet and 10% broccoli at 5 wk before induction with diethylnitrosamine at 6 wk (93).…”
mentioning
confidence: 99%
“…However, the development of nasal cavity neoplasm has not been reported for any route of DEN administration in the mouse model. As part of a larger study of the impact of DEN and a Western (high fat/ high sugar) diet on liver health (Chen et al , 2016), we observed difficulty in breathing in many DEN-treated animals, independent of dietary treatment. Here we report the appearance of multiple nasal epithelial neoplastic lesions, visible externally in only one instance, induced by intraperitoneal treatment with DEN.…”
Section: Introductionmentioning
confidence: 87%
“…Experimental design and diet formulae are described in a previous report (Chen et al , 2016) and summarized below. Seventy-two male 4-week-old B6C3F1 (male C3H/HeJ × female C57Bl/6J) mice were purchased from the Jackson Laboratory (Bar Harbor, ME, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation